A Work study on Ponderosa Leathergoods Co, Inc. - Herrera, Maria Cecilia; Jalandoni, Rafael; Mendoza, Paulino Jr; Romanes, Maia (College of Engineering, 1992)
The subject of the work study is Ponderosa Leather Goods, Inc., a company which manufactures baseball and hockey gloves for a foreign market. It is a labor-intensive enterprise operating on a job-order system. Glove materials which are largely imported pass through three production departments namely, Cutting, Assembly and Lacing/Packing, undergoing as much as forty processes depending on the style of the glove. The Assembly Department has four major and two minor lines, each of which caters to a different customer. The group concentrated on the Cutting and Assembly Departments for methods and systems study respectively. Through interviews and direct observations, the group has identified four general problem areas : 1) Layout 2) Methods and Procedures 3) Worker-Management relations and 4) Production Planning. These contribute to the over-all effect of the company not being able to meets shipping deadlines. In the formulation of alternatives, the group concentrated on dealing with the first three problem areas. New layouts were designed for the Cutting and Assembly Departments. Unnecessary processes were eliminated while new tools have been proposed. Measures were also put forth to improve management worker relationship. Included were improvements to be made on the working conditions within the plant. A Time Study was conducted to know the standard production capacity of the plant as well as to lend support to recommendations pertaining to machine and process standardization and worker incentive proposals.